The Utilization of Core Values as an Avenue for Promotion in Sport: Faith based Activations as the Moral Face of Sport Organization Brands - Michael Hutchinson (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2010)
The administration of and participation in present-day sport is inundated with situations requiring individuals with varying moral paradigms to determine appropriate action. The marketing discipline has drawn considerable attention from ethical decision makers, as marketing practitioners are responsible for satisfying both active and inactive consumer ‘needs.’ Traditional forms of promotion within the sport setting have focused on targeting fans through financial value, cost minimization, or product giveaways (e.g., Friday night fireworks, $1 hot dog night, bobble-head night). However, professional sport organizations have recently extended marketing endeavors to include faith based activations as a form of promotional strategy, accessing fans by means of their individual core values. The purpose of this paper is to propose a set of considerations for the proper utilization of fans’ core values and subsequently present a decision making model for application prior to implementing such a promotional strategy. There is relative paucity of original research examining sport marketers’ attempt to access fans core values via promotion in the sport setting. This paper will place particular emphasis on the considerations necessary for proper application of promotional campaigns targeting fans core values, via faith based activations, as the primary component for accessing target market segments. Acknowledgement of appropriate factors for consideration in application of a faith based promotional strategy and development of a related model for organizational application will be presented.
Keywords: Sport; faith-based; Sport brands; sport marketing